Health Information Systems - Toubiana, L.; Cuggia, M. (Yearbook of Medical Informatics, 2013)
Objectives: Summarize excellent current research in the field of Health Information Systems.Method: Synopsis of the articles selected for the IMIA Yearbook 2013.Results: Five papers from international peer reviewed journals have been selected for the section on health information systems.Conclusions: The selected articles illustrate current research regarding health information technology (IT) impacts and evaluation and the latest developments in health information exchange.
Keywords: Medical informatics; International Medical Informatics Association; health information systems,hospital information systems